Analyses of the Mode of Action of an Alpha-Adrenoceptor Blocker in Substantia Gelatinosa Neurons in Rats - Daisuke Uta (International Journal of Molecular Sciences, 2021)
To elucidate why naftopidil increases the frequency of spontaneous synaptic currents in only some substantia gelatinosa (SG) neurons, post-hoc analyses were performed. Blind patch-clamp recording was performed using slice preparations of SG neurons from the spinal cords of adult rats. Spontaneous inhibitory and excitatory postsynaptic currents (sIPSCs and sEPSCs, respectively) were recorded. The ratios of the frequency and amplitude of the sIPSCs and sEPSCs following the introduction of naftopidil compared with baseline, and after the application of naftopidil, serotonin (5-HT), and prazosin, compared with noradrenaline (NA) were evaluated. First, the sIPSC analysis indicated that SG neurons reached their full response ratio for NA at 50 μM. Second, they responded to 5-HT (50 μM) with a response ratio similar to that for NA, but prazosin (10 μM) did not change the sEPSCs and sIPSCs. Third, the highest concentration of naftopidil (100 μM) led to two types of response in the SG neurons, which corresponded with the reactions to 5-HT and prazosin. These results indicate that not all neurons were necessarily activated by naftopidil, and that the micturition reflex may be regulated in a sophisticated manner by inhibitory mechanisms in these interneurons.